Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ijsu.2017.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of delayed discharge after day-surgery laparoscopic cholecystectomy

Abstract: Patients who are delayed discharge due to psychosocial reasons have a rapid postoperative recovery. The slower postoperative recovery and upgraded complication classifications are related and optimized medical procedures promote the recovery. It is reasonable for patients who undergo conversion to open surgery to experience a slow postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…As the previously reported incidence of complications ranges from 4.8% to 15.7%, conversion to open surgery ranges from 0% to 3.0% and readmission ranges from 0% to 6.1%, 11–15,22,24 the differences between elderly patients and non‐elderly patients in this study in the incidence of complications (7.8% versus 7.9%), conversion to open surgery (0.7% versus 0.5%) and readmission within 30 days after discharge (0.5% versus 0.4%) were not statistically significant, which suggested no higher risk of these outcomes in elderly patients undergoing ALC. Additionally, Clavien‐Dindo I and II complications accounted for 92.2% of postoperative complications in elderly patients (Fig.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…As the previously reported incidence of complications ranges from 4.8% to 15.7%, conversion to open surgery ranges from 0% to 3.0% and readmission ranges from 0% to 6.1%, 11–15,22,24 the differences between elderly patients and non‐elderly patients in this study in the incidence of complications (7.8% versus 7.9%), conversion to open surgery (0.7% versus 0.5%) and readmission within 30 days after discharge (0.5% versus 0.4%) were not statistically significant, which suggested no higher risk of these outcomes in elderly patients undergoing ALC. Additionally, Clavien‐Dindo I and II complications accounted for 92.2% of postoperative complications in elderly patients (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Our study showed that all 1143 elderly patients undergoing ALC were cured, and the incidence of postoperative discharge within 24 h was 75.5%. The reasons for delayed discharge included psychosocial reasons, complications, drainage and conversion to open surgery, all of which have been reported in other studies 13–15,22,23 . There were fewer elderly patients than non‐elderly patients with postoperative discharge within postoperative 24 hours (75.5% versus 81.7%), which mainly resulted from the higher incidence of delayed discharge due to drainage (7.8% versus 3.2%) in elderly patients than in non‐elderly patients.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Classical discharge criteria are still valid to secure safe and effective discharge following surgery/anesthesia. Commonly described limiting factors for failed early discharge are; not showing robust stable vital signs, not being able to control of pain and PONV with oral medications not able to ambulation unaided and, not being adequately cognitive restored to manage self-care, patient and caregivers uncertainty to leave hospital [20 ▪▪ ,64,65]. Not being able to urinate and/or urinary retention is also a frequent failure course [66,67 ▪ ,68 ▪ ].…”
Section: Logisticsmentioning
confidence: 99%
“…Approximately one-half of the patients (44%) living at home before surgery were discharged to rehabilitation facilities after surgery (19). Other areas of research, such as day-surgery laparoscopic cholecystectomy, have reported some factors responsible for delayed discharge, including psychosocial factors (20). On the one hand, patients usually believe that they should get more professional care than unsupervised rehabilitation at home.…”
Section: Psychological Factorsmentioning
confidence: 99%